Implications of Vertebrate Craniodental Evo‐Devo for Human Oral Health. Issue 4 (2nd March 2017) - Boughner, Julia C.
GRAPHICAL ABSTRACT: Molar impaction, malocclusion, and jaw joint disorders are born of human morphological Evo‐Devo grating against sociocultural Evo. What we eat and how we chew may underpin widespread oral pathoses. Oral function is a promising noninvasive clinical target. ABSTRACT: Highly processed diets eaten by postindustrial modern human populations coincide with higher frequencies of third molar impaction, malocclusion, and temporomandibular joint disorders that affect millions of people worldwide each year. Current treatments address symptoms, not causes, because the multifactorial etiologies of these three concerns mask which factors incline certain people to malocclusion, impaction, and/or joint issues. Deep scientific curiosity about the origins of jaws and dentitions continues to yield rich insights about the developmental genetic mechanisms that underpin healthy craniodental morphogenesis and integration. Mounting evidence from evolution and development (Evo‐Devo) studies suggests that function is another mechanism important to healthy craniodental integration and fit. Starting as early as weaning, softer diets and thus lower bite forces appear to relax or disrupt integration of oral tissues, alter development and growth, and catalyze impaction, malocclusion, and jaw joint disorders. How developing oral tissues respond to bite forces remains poorly understood, but biomechanical feedback seems to alter balances of local bone resorption and deposition at the tooth–bone interface as well as affect tempos and amounts of facial outgrowth. Also, behavioral changes in jaw function and parafunction contribute to degeneration and pain in joint articular cartilages and masticatory muscles. The developmental genetic contribution to craniodental misfits and disorders is undeniable but still unclear; however, at present, human diet and jaw function remain important and much more actionable clinical targets. New Evo‐Devo studies are needed to explain how function interfaces with craniodental phenotypic plasticity, variation, and evolvability to yield a spectrum of healthy and mismatched dentitions and jaws.